Politeness Strategy in Interlanguage Pragmatics of Making Request Performed by Indonesian Young Child - Fais Wahidatul Arifatin (Journal of Social, Culture, and Language, 2024)
Since oral language is related with the sounds that convey meaning, a child must be a remarkable subject to be observed in using it in social interaction. Then surely a child must acquire pragmatic competence. Speech act are commonly given to specific labels such as apology, complaint, compliment, invitation, promise, or request’. Request is the first focus of this research. Afterward, regarding relative distance, a child needs to know a range of ways in making request politely. Thus, other pragmatic competence like using several different politeness strategies needs to be performed by a child. In this case, this paper attempts to answer the following research question: How does a bilingual child negotiate meanings involved in interlanguage pragmatics of request in a casual conversation? The subject of this paper is a bilingual child from Mondial Education who has English as a medium of instruction being spoken three hours a day at school and the data is in the form of transcription, both of them were taken from related research journal. The transcription was then analyzed and interpreted. The findings show that the subject that use English as second language are able to use various politeness strategy but fail to gain awareness of social distance (relative distance).